Early Effects of Passive Leg-Raising Test, Fluid Challenge, and Norepinephrine on Cerebral Autoregulation and Oxygenation in COVID-19 Critically Ill Patients - Robba, Chiara; Messina, Antonio; Battaglini, Denise; Ball, Lorenzo; Brunetti, Iole; Bassetti, Matteo; Giacobbe, Daniele R.; Vena, Antonio; Patroniti, Nicolo'; Cecconi, Maurizio; Matta, Basil F.; Liu, Xiuyun; et al. (Frontiers in Neurology, 2021)
Background: Coronavirus disease 2019 (COVID-19) patients are at high risk of neurological complications consequent to several factors including persistent hypotension. There is a paucity of data on the effects of therapeutic interventions designed to optimize systemic hemodynamics on cerebral autoregulation (CA) in this group of patients. Methods: Single-center, observational prospective study conducted at San Martino Policlinico Hospital, Genoa, Italy, from October 1 to December 15, 2020. Mechanically ventilated COVID-19 patients, who had at least one episode of hypotension and received a passive leg raising (PLR) test, were included. They were then treated with fluid challenge (FC) and/or norepinephrine (NE), according to patients' clinical conditions, at different moments. The primary outcome was to assess the early effects of PLR test and of FC and NE [when clinically indicated to maintain adequate mean arterial pressure (MAP)] on CA (CA index) measured by transcranial Doppler (TCD). Secondary outcomes were to evaluate the effects of PLR test, FC, and NE on systemic hemodynamic variables, cerebral oxygenation (rSo2), and non-invasive intracranial pressure (nICP). Results: Twenty-three patients were included and underwent PLR test. Of these, 22 patients received FC and 14 were treated with NE. The median age was 62 years (interquartile range = 57–68.5 years), and 78% were male. PLR test led to a low CA index [58% (44–76.3%)]. FC and NE administration resulted in a CA index of 90.8% (74.2–100%) and 100% (100–100%), respectively. After PLR test, nICP based on pulsatility index and nICP based on flow velocity diastolic formula was increased [18.6 (17.7–19.6) vs. 19.3 (18.2–19.8) mm Hg, p = 0.009, and 12.9 (8.5–18) vs. 15 (10.5–19.7) mm Hg, p = 0.001, respectively]. PLR test, FC, and NE resulted in a significant increase in MAP and rSo2. Conclusions: In mechanically ventilated severe COVID-19 patients, PLR test adversely affects CA. An individualized strategy aimed at assessing both the hemodynamic and cerebral needs is warranted in patients at high risk of neurological complications.